Combined Estrogen Alpha and Beta Receptor Expression Has a Prognostic Significance for Colorectal Cancer Patients - Topi, Geriolda; Ghatak, Souvik; Satapathy, Shakti Ranjan; Ehrnström, Roy; Lydrup, Marie-Louise; Sjölander, Anita (Frontiers in Medicine, 2022)
We have previously reported that high estrogen receptor beta (ERβ) expression is independently associated with better prognosis for female colorectal cancer (CRC) patients. Whereas estrogen receptor alpha (ERa) is expressed at very low levels in normal colon mucosa, and its prognostic role in CRC has not been explored. Herein, we investigated the combined role of ERa and ERβ expression in the prognosis of CRC female patients, which, to the best of our knowledge, is the first study. A total number of 306 primary CRCs were stained for ERa and ERβ expression. A Cox regression model was used to evaluate overall survival (OS) and disease-free survival (DFS). The combined high ERβ and negative ERa expression correlated with longer OS [HR (95% CI) 0.23 (0.11-0.45), P <0.0001] and DFS [HR (95% CI 0.10 (0.03-0.26), P <0.0001], and significant higher expression of anti-tumorigenic proteins than combined low ERβ and positive ERa expression. Overall, our results show that the combined high ERβ and negative ERa expression correlated with a better prognosis for CRC patients. We suggest that the combined expression of ERβ and ERa could be used as a marker for prediction of OS and DFS for CRC patients.